2009
DOI: 10.1590/s1516-35982009001200020
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de frangos de corte consumindo rações contendo sorgo e gérmen integral de milho

Abstract: RESUMO -Avaliou-se a substituição do sorgo pelo gérmen integral de milho em rações para frangos de corte. Foram conduzidos dois experimentos, em delineamento inteiramente casualizado com quatro níveis de substituição do sorgo pelo gérmen integral de milho (0; 33,3; 66,7 e 100%) como concentrado energético em rações com ingredientes de origem vegetal (experimento 1) ou de origem animal (experimento 2), cada um com quatro repetições. Avaliaram-se o desempenho (ganho de peso, consumo de ração e conversão alimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Those authors argue that the obtained results are due to the similar nutritional values of corn and sorghum, and therefore, it is possible to formulate diets with close nutritional values, especially for metabolizable energy and amino acids using both sorghum and corn. Although literature results are controversial (Santos, 2006;Rocha et al, 2008;Stringhini et al, 2009), in general, the replacement of corn by sorghum in broiler diets does not compromise performance, as observed in the present study.…”
Section: Implications Of the Use Of Sorghum In Broiler Productionsupporting
confidence: 67%
See 1 more Smart Citation
“…Those authors argue that the obtained results are due to the similar nutritional values of corn and sorghum, and therefore, it is possible to formulate diets with close nutritional values, especially for metabolizable energy and amino acids using both sorghum and corn. Although literature results are controversial (Santos, 2006;Rocha et al, 2008;Stringhini et al, 2009), in general, the replacement of corn by sorghum in broiler diets does not compromise performance, as observed in the present study.…”
Section: Implications Of the Use Of Sorghum In Broiler Productionsupporting
confidence: 67%
“…On the other hand, Stringhini et al (2009) found a quadratic effect on broiler final weight and weight gain, when corn was replaced by sorghum at levels of 21.03% to 21.68% compared with the other tested diets with high percentage of addition of sorghum; however, the tested diets did not affect other performance parameters or carcass yield. The results of Robertson & Perez-Maldonado (2006) showed worse feed conversion ratio when broilers were fed a sorghum-based diet than with corn based diet.…”
Section: Implications Of the Use Of Sorghum In Broiler Productionmentioning
confidence: 77%
“…The results of our study are consistent with previous reports of others (Garcia et al, 2013;Torres et al, 2013;Stringhini et al, 2009;Rocha et al, 2008;Santos et al, 2006) who did not find any differences in feed intake, weight gain or feed conversion when evaluating the growth performance of broilers fed sorghum as partial corn replacement in diets. Zarghi and Golian, (2009) also, revealed that 50% corn replacement with triticale had no negative effect on broiler growth performance.…”
Section: Growth Performancesupporting
confidence: 93%